Study of BBB Dysregulation in Neuropathogenicity Using Integrative Human Model of Blood–Brain Barrier - Simöes Da Gama, Coraly; Morin-Brureau, Mélanie (Frontiers in Cellular Neuroscience, 2022)
The blood–brain barrier (BBB) is a cellular and physical barrier with a crucial role in homeostasis of the brain extracellular environment. It controls the imports of nutrients to the brain and exports toxins and pathogens. Dysregulation of the blood–brain barrier increases permeability and contributes to pathologies, including Alzheimer's disease, epilepsy, and ischemia. It remains unclear how a dysregulated BBB contributes to these different syndromes. Initial studies on the role of the BBB in neurological disorders and also techniques to permit the entry of therapeutic molecules were made in animals. This review examines progress in the use of human models of the BBB, more relevant to human neurological disorders. In recent years, the functionality and complexity of in vitro BBB models have increased. Initial efforts consisted of static transwell cultures of brain endothelial cells. Human cell models based on microfluidics or organoids derived from human-derived induced pluripotent stem cells have become more realistic and perform better. We consider the architecture of different model generations as well as the cell types used in their fabrication. Finally, we discuss optimal models to study neurodegenerative diseases, brain glioma, epilepsies, transmigration of peripheral immune cells, and brain entry of neurotrophic viruses and metastatic cancer cells.